External debt accumulation and economic growth: evidence from West African countries (2015)
This paper investigates how indebtedness has affected the growth of 14 West African countries directly, and via investment and fiscal balance mechanisms, using data from 1970 to 2012. This task was approached through a standard growth framework through which debt indicators were incorporated. Two econometric specifications (linear and non-linear.) were used, and evaluated with the fixed effects and GMM estimation techniques on the relationship between debt and growth. The hypothesis that external debt affects growth is well-supported by the results. All debt variables have the expected signs and were statistically significant. The results reveal that debt appears to have a non-linear effect on growth. The debt overhang hypothesis is affirmed, given the existence of a threshold beyond which debt negatively contributed to growth. The average impact of debt on per capita growth becomes negative for debt levels above 60% to 74% of GDP. Thus, increasing debt beyond this threshold yields a negative marginal contribution to growth. There is a pressing need to take measures to not only stabilize external debts, but to place them on a downward trajectory in the future.